2019
DOI: 10.15789/2220-7619-2019-2-354-362
|View full text |Cite
|
Sign up to set email alerts
|

The problem of pertussis in some regions of the world

Abstract: Pertussis infection remains a high-priority issue both for Russian health care and abroad. A rise of pertussis incidence in various human age groups instigates a search for new ways to fight this infection and improve methods for its laboratory diagnostics. By taking into consideration a short-term effect induced by acellular and whole-cell vaccines, a feasibility of introducing the second or even the third pertussis revaccination is vigorously debated. Objective of the study was to analyze the experience and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 21 publications
0
1
0
1
Order By: Relevance
“…Articles identified for the systematic review A total of 2,648 non-duplicate references were identified, and, after screening based on titles and abstracts (first phase), 517 were retained for further assessment. Although the searches were done without language restriction, seven articles had to be excluded because they were written in languages not read by the authors (two Chinese 21,22 , two German 23,24 , onw Russian 25 and two in Uzbek 26,27 . After full texts were assessed (second phase), a total of 12 studies [28][29][30][31][32][33][34][35][36][37][38][39] met the inclusion criteria.…”
Section: Vaccines Currently In Usementioning
confidence: 99%
“…Articles identified for the systematic review A total of 2,648 non-duplicate references were identified, and, after screening based on titles and abstracts (first phase), 517 were retained for further assessment. Although the searches were done without language restriction, seven articles had to be excluded because they were written in languages not read by the authors (two Chinese 21,22 , two German 23,24 , onw Russian 25 and two in Uzbek 26,27 . After full texts were assessed (second phase), a total of 12 studies [28][29][30][31][32][33][34][35][36][37][38][39] met the inclusion criteria.…”
Section: Vaccines Currently In Usementioning
confidence: 99%
“…Это происходит несмотря на высокий охват вакцинацией детского населения и введения в ряде стран ревакцинации подростков и взрослых. Вплоть до 2003 г. единственной группой риска по коклюшу были дети до года, с 2007 года второе место по рейтингу заняли дети школьного возраста -7-10 лет [4,5].…”
Section: практические аспекты эпидемиологии и вакцинопрофилактики Praunclassified